FINANCING HEALTHCARE SYSTEM IN AZERBAIJAN AND FUTURE PERSPECTIVES OF IMPLEMENTATION COMPULSORY HEALTH INSURANCE MECHANISM (International Journal of Innovative Technologies in Economy, 2020)
Insurance relations are one of the most important elements of the market relations system. In the context of market relations, the principles of insurance, development of insurance market and expansion of insurance services are important factors. The study was aimed to determine the ways of attracting resources for the protection, strengthening and provision of health care of population by the means of health insurance.Furthermore, the value and quality of resources allocated by both state and other market players, and the effectiveness of their use in the health sector have been analyzed. Moreover, the fundamental models that considered as a ground for different insurance systems has been superficially touched by the author. The mechanism of applying compulsory health insurance in Azerbaijan as a pilot project and the project’s outcomes were taken into consideration while conducting a research.